Welfare Rules, Incentives, and Family Structure - Robert A. Moffitt; Brian J. Phelan; Anne E. Winkler (Institute for the Study of Labor (IZA), 2015)
In this study we provide a new examination of the incentive effects of welfare rules on family structure. Focusing on the AFDC and TANF programs, we first emphasize that the literature, by and large, has assumed that the rules of those programs make a key distinction between married women and cohabiting women, but this is not a correct interpretation. In fact, it is the biological relationship between the children and any male in the household that primarily determines how the family is treated. In an empirical analysis conducted over the period 1996 to 2004 that correctly matches family structure outcomes to welfare rules, we find significant effects of several welfare policies on family structure, both work-related policies and family-oriented policies, effects that are stronger than in most past work. Many of our significant effects show that these rules led to a decrease in single motherhood and an increase in biological partnering. For all of our results, our findings indicate that the impact of welfare rules crucially hinges on the biological relationship of the male partner to the children in the household.
Keywords: I3; J1; 330; welfare; family